1981
DOI: 10.1523/jneurosci.01-06-00596.1981
|View full text |Cite
|
Sign up to set email alerts
|

Localization of cholinesterase at sites of high acetylcholine receptor density on embryonic amphibian muscle cells cultured without nerve

Abstract: Myotomal muscle cells, derived from Xenopus embryos and grown in culture without nerve, develop discrete sites of cholinesterase (ChE) activity on their surface. The spatial relationship of these ChE patches to surface patches of acetylcholine receptors (AChRs) has been examined in the present study by a combination of ChE histochemistry and fluorescent staining of the receptors. ChE patches and AChR patches developed as early as the 1st day in culture and exhibited a high incidence of spatial overlap. The fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…The 43-kDa protein shares the property of many postsynaptic components in that it is concentrated at sites of high AcChoR density in muscle cells cultured in the absence of neurons (20)(21)(22). The information required for assembling much of the postsynaptic structure is apparently intrinsic to the muscle cell; motor neurons, however, can trigger this process to occur at synaptic sites.…”
Section: Discussionmentioning
confidence: 99%
“…The 43-kDa protein shares the property of many postsynaptic components in that it is concentrated at sites of high AcChoR density in muscle cells cultured in the absence of neurons (20)(21)(22). The information required for assembling much of the postsynaptic structure is apparently intrinsic to the muscle cell; motor neurons, however, can trigger this process to occur at synaptic sites.…”
Section: Discussionmentioning
confidence: 99%
“…Such a mechanism has also been implicated in a study of ectopic reinnervation of adult denervated muscle in vivo (L0mo & Slater, 1980) and is supported by cross-innervation experiments which indicate that the nerve regulates the distribution of synaptic contacts along embryonic chick muscle fibres (Bennett & Pettigrew, 1974b). On the other hand, ACh receptor patches can form on cultured muscle cells in the absence of innervation or previous contact by nerve (Bekoff & Betz, 1976;Moody-Corbett & Cohen, 1981) and the site of their formation can be determined by non-neuronal factors (Peng, Cheng & Luther, 1981). Widespread ACh receptor patches also form on denervated muscle in vivo (Ko, Anderson & Cohen, 1977;Harris, 1981c;Steinbach, 1981 b), as well as on paralysed fetal muscle in vivo (Harris, 1981c).…”
mentioning
confidence: 86%
“…However, on the basis of our findings it would appear that the presence of nerve fibres is not obligatory for the expression of ACh receptor on developing muscle cells in vivo. Studies on appropriate cell cultures have likewise indicated that expression of ACh receptors and other aspects of muscle differentiation can occur in the absence of any previous contact by nerve fibres (Bekoff & Betz, 1976;Moody-Corbett & Cohen, 1981). It should be noted, however, that presumptive and developing muscle cells and spinal cord are located close to each other in young embryos.…”
Section: Acquisition Of Ach Receptorsmentioning
confidence: 99%
“…stances codistributing with clusters of AChR include basal lamina antigens [3,41], acetyl cholinesterase [33], actin [25], vinculin [4], and laminin [10], The present study demon strates additional differences in carbohydrate content between extraneous coats associated with a high density of immobile receptors and the general cell surface which contains lowdensity, mobile receptors.…”
mentioning
confidence: 83%